Longitudinal Physical Activity Change During Hemodialysis and Its Association With Body Composition and Plasma BAIBA Levels - Molfino, Alessio; Amabile, Maria Ida; Ammann, Thomas; Lai, Silvia; Grosso, Alessandra; Lionetto, Luana; Spagnoli, Alessandra; Simmaco, Maurizio; Monti, Massimo; Laviano, Alessandro; Chiappini, Maria Grazia; Muscaritoli, Maurizio (Frontiers in Physiology, 2019)
Rationale: Low physical activity is frequent in end stage renal disease. We evaluated the longitudinal change in physical activity and its barriers in hemodialysis (HD) patients and the association between the patterns of physical activity change, body composition, and beta-aminoisobutyric acid (BAIBA), as circulating myokine. Methods: This is an observational study, where HD patients were considered in a 24-month follow-up. We assessed overtime the change of physical inactivity and its barriers by validated questionnaires, body composition by bioimpedance analysis, muscle strength by hand-dynamometer, and plasma BAIBA levels by liquid chromatography spectrometry. Parametric and non-parametric analyses were performed, as appropriate. Results: Out of the 49 patients studied at baseline, 39 completed the first-year follow-up, and 29 completed the second year. At month 12, active patients had higher intracellular water (ICW) (P = 0.001) and cellular mass (P < 0.001), as well as at month 24 (P = 0.012, P = 0.002; respectively) with respect to inactive. A significant reduction in ICW was shown at month 12 (P = 0.011) and month 24 (P = 0.014) in all patients. The barrier “reduced walking ability” was more frequent in inactive patients with respect to active at month 12 (P = 0.003) and at month 24 (P = 0.05). At month 24, plasma BAIBA levels were higher among active patients with respect to inactive (P = 0.043) and a correlation was seen between muscle strength and ICW (r = 0.51, P = 0.005); normalizing BAIBA per body mass index, we found it lower with respect to baseline (P = 0.004), as well as after correcting per ICW (P = 0.001), as marker of muscle mass. Conclusion: A high prevalence of physical inactivity persisted during a 24-month follow-up in this cohort. We found an association between physical activity and a decline in marker of muscularity and reduced plasma BAIBA levels.